2013
DOI: 10.1111/jpim.12122
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Distance and Team Collaboration in Distributed Teams

Abstract: This paper challenges the conventional wisdom that objective distance between team members (e.g., measured in miles) translates directly and fully into subjective distance (i.e., a team's perception of distance between its members). Drawing on social information processing theory, we argue that the level of subjective distance is likely to predict important team outcomes better than the level of objective distance. Using responses from 678 team leaders and team members pertaining to 161 new product development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 68 publications
(138 reference statements)
1
50
0
Order By: Relevance
“…Here, methods focus more on groups of tasks or other process elements supported by micro--scale processes. This scale draws on mid--level theory such as organisational or group information processing (Hult, Ketchen, & Slater, 2004;Siebdrat, Hoegl, & Ernst, 2013), communication dynamics (Maier, Eckert, & Clarkson, 2005), or decision making (Schmidt, Montoya--Weiss, & Massey, 2001). For example, Robinson (2010) highlights a number of key features of information behaviour and how it changes over time.…”
Section: Meso--scalementioning
confidence: 99%
See 1 more Smart Citation
“…Here, methods focus more on groups of tasks or other process elements supported by micro--scale processes. This scale draws on mid--level theory such as organisational or group information processing (Hult, Ketchen, & Slater, 2004;Siebdrat, Hoegl, & Ernst, 2013), communication dynamics (Maier, Eckert, & Clarkson, 2005), or decision making (Schmidt, Montoya--Weiss, & Massey, 2001). For example, Robinson (2010) highlights a number of key features of information behaviour and how it changes over time.…”
Section: Meso--scalementioning
confidence: 99%
“…As such, identifying relevant theoretical models for this wider group of processes e.g. Information processing theory (Siebdrat et al, 2013), may pave the way to richer description of design as a cohesive process. For example, the multi--scale processes described here suggest that C--K would need to be combined with other models at different levels of activity in order to fully explain and predict design behaviour in detail.…”
Section: Multi--scale Embedded Processesmentioning
confidence: 99%
“…As an example, O'Leary and Cummings (2007) and Schweitzer and Duxbury (2010) deployed purely objective measures for assessing distance among members as a contributor to virtuality. On the contrary, Siebdrat, Hoegl, and Ernst (2014) asserted that perceptive distance is the measure affecting virtuality in teams.…”
Section: Author (Year)mentioning
confidence: 96%
“…This endorsed the fact that the virtuality of a team based on the conceptual model in Figure 5 should be assessed taking into account the context and the conditions of the team as asserted by Arora et al (2012). In this regard, , Watson-Manheim, Chudoba, and Crowston (2012) and Siebdrat, Hoegl, and Ernst (2014) suggested that there are glaring differences between objective virtuality factors (such as distance) and the ones perceived by members of teams, which are the main factors affecting the quality of communications in teams. Therefore, it is contended that validating the model of this study should draw upon the perception of members of teams.…”
Section: Conceptual Model Of Team Virtualitymentioning
confidence: 96%
See 1 more Smart Citation